The Unknown as an Engine for Science: An Essay on the Definite and the Indefinite - Pirner, Hans J (Springer, 2015)
This book explores the limits of our knowledge. The author shows how uncertainty and indefiniteness not only define the borders confining our understanding, but how they feed into the process of discovery and help to push back these borders. Starting with physics the author collects examples from economics, neurophysiology, history, ecology and philosophy.